Review Report on Factors Affecting Labour Productivity in RCC Work: An Analysis of Factors Influencing Labour Productivity in RCC Work (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Construction is one of the major and most challenging industries in the World. In Construction Industry labour productivity is at the serious concern faced by the professionals while implementingexecuting the work. Labour Productivity is a crucial role in defining the financial effect of any construction project. Every Project Costs labour about 35 to 50 of entire Construction Phases. The utmost challenging subject in Construction business is to increase the Construction labour Productivity. In past many researches have been done, however a detail study is still needed to improve the labour productivity. The productivity of labour is primarily important in developing countries like India, where total construction work is still on Labour basis. The objective of the study is to get the up-to date data and to find the key factors that affect the labour productivity. It highlights Construction Labour Productivity Definitions, Aspects, and Factors affecting it.